Utjecaj saobraćaja na razvoj turizma u gravitacionom području pruge Beograd-Bar - DOKIĆ, Mirko (Promet - Traffic&Transportation, 2026)
IMPACTS OF TRANSPORT UPON TOURIST INDUSTRY DEVELOPMENT IN THE BEOGRAD–BAR LINE GRAVITATION REGION The author reiterates the requirement for improvement of the Beograd-Bar railway line as an important element of development of tourist industry and services in its gravitation region. In this respect, the paper advocates the logistic support of activities aimed at the advancement of this traffic route, requirement for construction of access lines, and pleads for a more intense cooperation of the port of Bar with Southern Italy, employment of ferry-boat services on the Bar–Bari route.